Pandemic and post-pandemic: Mental Health and life conditions of venezuelan migrants in America - Alarcón, Renato D. (2025)
At the start of the COVID-19 pandemic around the world, the number of Venezuelan migrants in Latin Americancountries reached about 5 million. Contagiousness, quarantines, and deaths dramatically impacted their life, affectedtheir mental health and made their future difficult and uncertain. This report attempts to determine the impact ofCOVID-19 on Venezuelan migrants in Colombia, Ecuador, Peru (65 % of the total) and other countries in the Americancontinente, gathering information on resulting social behaviors, mental health problems, and bases of eventual solutions.It is a narrative review, based on material from established bibliographic sources, reliable reports from academicinstitutions and specialized international agencies on qualitative and quantitative analyses of areas such as living conditions, education, social mobility, vulnerabilities and physical and mental health in the migrant population. About one-third of the migrants were infected by COVID-19, and close to 2% (~ 100.000) died as a result. Their emotional stability and quality of life went below those of the host countries' poorest population groups, increasing their vulnerability and inducing, in a good number of cases, a return to Venezuela. A variety of adverse events (personal, familial, social, political, or economic) converged on the decision to migrate, during the migration process itself and in the host countries, generating multiple risks and suffering experiences, extended to the post-pandemic phase. The management of this complex situation demands solid and effective policies, efficient health services, and educational, community-oriented solidarity campaigns aimed at the protection of migrant populations' integral health, and at a harmonious social exchange between migrants and host populations.